New Techniques for Prevention and Treatment of Oral Bacterial Diseases - Zhang, Jin (International Journal of Public Health and Medical Research, 2024)
Oral bacterial diseases include caries, periodontal disease, gingivitis, and oral cancer, and they are usually associated with an imbalance in the regulation of the oral microbiota. In the prevention and treatment of oral bacterial diseases, in addition to good oral hygiene habits and traditional treatments, studies have shown that a variety of emerging technologies, such as gingival mesenchymal stem cells (GMSCs), novel nanomaterial-based antibacterial photodynamic therapies, fluorescence molecular imaging, programmed death receptor ligand-1 positron emission tomography (PD-L1 PET), and so on, have shown high efficacy in the treatment of oral and bacterial diseases. Bacterial diseases have demonstrated high efficiency, safety, and personalized therapeutic effects. However, there are limitations such as the lack of large-scale clinical trials for many of these technologies.